Growth and Yield of Soybean (Glycine max L. Merill) at Various Doses of Bokashi Fertilizer on Ultisol - Luki Rianti; Hesti Pujiwati; Masdar Masdar; Hermansyah Hermansyah; Heru Widiyono (TERRA : Journal of Land Restoration, 2021)
Soybean is a type of secondary crop that is widely cultivated and used as raw material for tofu, tempe, milk, and so on by the people of Indonesia. Soybean consumption is always increasing but soybean production has decreased. This study aims to obtain the optimum dose of Bokashi fertilizer on plant growth and yield in Ultisol. The study was carried out in Medan Baru, Kandang Limun Village, Muara Bangkahulu District, Bengkulu City from December 2018 to April 2019. This study used a Completely Randomized Block Design (RCBD) with one factor, namely the dose of Bokashi fertilizer with five levels, namely 0 tons ha-1, 25 tons ha-1, 35 tons ha-1, 45 tons ha-1, and 55 tons ha-1. The results showed that the optimum dose of Bokashi fertilizer was not found in the growth component or yield component. The dose of Bokashi fertilizer had a significant effect (p<0.05) on the growth of Bokashi and the number of leaves.